Implementing Quizlet for Improving EFL Students’ Vocabulary Learning Within Flipped Classroom - Al Falah Muhammad, Fawwaz; Rochmah, Noviatul; Asmara, Candra Hadi (Universitas Muhammadiyah Gresik, 2024)
This English language learning initiative, focused on acquiring new vocabulary, implemented a Flipped Classroom approach utilizing Quizlet as a Mobile-Assisted Language Learning (MALL) program for the experimental group. The research took place at SMA Muhammadiyah 1 Gresik, East Java, Indonesia, during the 2023/2024 academic year. The homogeneity of the 59 samples was verified through Levene's test, with a significance value of 0.060 based on average pre-test scores, indicating homogeneity as the significance level was >0.05. Subsequently, pre-test and post-test data were collected from 12th-grade students in the social sciences and humanities (IPS/Shosum) program. Descriptive statistics were applied to analyze both groups' pre-test and post-test data, along with the non-parametric Mann Whitney T-Test, resulting in an Asymp. Sig. (2-tailed) value of 0.071, indicating rejection of the alternative hypothesis as it exceeded 0.05. Nevertheless, it is imperative to address various aspects in future research and practice to explore further potential benefits or drawbacks of incorporating Quizlet in the flipped classroom, including aspects like student engagement, motivation, and long-term retention of material. Additionally, subsequent studies could delve into evaluating the effectiveness of combining Quizlet with other instructional methods or technologies within the flipped classroom framework.